Nurses’s knowledge about the management of pregnant with positive VDRL - Andrade, Roumayne FV; Lima, Nara BG; Araújo, Maria AL; Silva, Denise MA; Melo, Simone P (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: syphilis remains as a serious public health problem, considering the repercussions that may result in the fetus when the pregnant woman does not received treatment or is inadequately treated. Objective: analyzed the knowledge of the Family Health Strategy nurses from Fortaleza-Ceará about the prevention actions, treatment, and control of syphilis during pregnancy. methods: an evaluative study, performed during the months of August and September 2010, which sample was composed by 160 nurses. It was used a self-applied questionnaire, elaborated based on the Health Office recommendations for the control of syphilis during pregnancy and congenital syphilis. The answers in agreement with Health Office preconizes were considered correct. Socio-demographic data and variables related to diagnosis, treatment and the follow-up of pregnant women with positive VDRL were analyzed. results: they don’t have knowledge about treponemic and non-treponemic types of serology 76,2% of the nurses, 83,7% about conduct facing VDRL titles, 59,4% about secondary disease treatment and 66,9% about recent syphilis phases identification. Conclusion: the Family Health Strategy nurses don’t have the suitable knowledge about preventing and controlling actions on the pregnant woman.